Dictionary of Christianity and science : the definitive reference for the intersection of Christian faith and contemporary science - Copan, Paul; Longman, Tremper, III; Reese, Christopher L.; Strauss, Michael G. (Grand Rapids, Michigan : Zondervan, 2017)
How does Christian theology relate to scientific inquiry? What are the competing philosophies of science, and do they "work" with a Christian faith based on the Bible? No reference work has covered this terrain sufficiently--until now. Featuring the work of over 140 international contributors, the Dictionary of Christianity and Science is a deeply-researched, peer-reviewed, fair-minded work that illuminates the intersection of science and Christian belief. In one volume, you get reliable summaries and critical analyses of over 450 relevant concepts, theories, terms, movements, individuals, and debates. You will find answers to your toughest questions about faith and science, from Adam and Eve and the Age of the Earth to Evolution and String Theory. -- Amazon.com
Includes bibliographical references.
Keywords: Religion and science -- Dictionaries; Theology -- Dictionaries